Introduction of high-resolution anorectal manometry in Cuba. First outcomes - Vivianne Anido Escobar; Zunilda Díaz Drake; Tatiana Amable Díaz; Mildred Armenteros Torres; Maydolis Labrada Sosa; Jorge A, Ávila Anido (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: High-resolution anorectal manometry has allowed a better understanding of the pathophysiology of motor and sensory damage in patients with pelvic floor dysfunction. Objective: To offer the outcomes of the introduction of the technique applied in a first group of patients in Cuba, as well as its characterization, the values obtained for the study parameters and the most frequent diagnoses. Material and Methods: The high-resolution anorectal manometry records, which were performed at the CNCMA Motility Laboratory between September 2017 and June 2019, were reviewed. The record of the patients´ general data and specific discharge parameters were analyzed. The London Classification was applied for the diagnosis of the resulting type of anorectal dysfunction. Results: A total of 159 patients were studied.  There was a predominance of females over 60 years of age. The most common indication for the test was fecal incontinence, followed by constipation. Obstetric history or history of surgical intervention were frequent in women. Type III dyssynergia was the most frequent type of dyssynergic defection. The most frequent diagnoses of anorectal dysfunction were disorders of anal tone and contractility. Conclusions: The introduction of the technique was successful.  It allowed the identification of the damaged structures, which led to a faster and more timely therapeutic decision-making for the patient. The London Classification was used in the diagnosis of dysfunction.